The growth and development of the beef qualities of Angoni cattle (East African zebu). Part 2. Linear growth and carcass characteristics - Walker, C.A. (Cambridge University Press, 1964)
Proportional growth as is shown by linear growth and carcass characters in Angoni cattle were investigated. The growth of all sexes showed three typical waves of bone, muscle and fat development. The dressing percentage rose steadily from birth to 5 months irrespective of sex. The Angoni showed a high potential for meat production, particularly under well-managed natural environmental conditions. Adaptation was the main constraint but it did not interfere seriously with its potential development.